Level of Stress and Job Satisfaction among Call Operators: A Case of Malaysian Telecommunication Sector - Memon, Mumtaz Ali; Ting, Hiram; Salleh, Rohani; Ali, Jati Kasuma; Yacob, Yusman (International Review of Management and Marketing, 2016)
The study aims to identify the level of stress and job satisfaction among call operators (COs) in Malaysia. It also explores COs views on the factors affecting their stress level and job satisfaction. This research is based on a case study of a telecommunication contact centre. A mixed-methods design was employed whereby a survey questionnaire was completed by 113 COs, and two in-depth interviews were conducted. The results indicate the reasons and potential outcomes of high level stress and low job satisfaction among COs. Stressful working environment, poor supervisory support, and heavy workload are found to be key factors affecting COs high level of stress and low job satisfaction. As such the study provides valuable insights to researchers and practitioners. Keywords: Contact centre, Call Operators, Job Satisfaction, Stress, Mixed-Method Design JEL Classification: M12